Revisiting the phylogeny of Ocellularieae, the second largest tribe within Graphidaceae (lichenized Ascomycota: Ostropales) - Kraichak, Ekaphan; Parnmen, Sittiporn; Lücking, Robert; Plata, Eimy Rivas; Aptroot, André; Cáceres, Marcela E. S.; Ertz, Damien; Mangold, Armin; Mercado-Díaz, Joel A.; Papong, Khwanruan; Broeck, Dries Van Den; Weerakoon, Gothamie; et al. (Phytotaxa, 2014)
We present an updated 3-locus molecular phylogeny of tribe Ocellularieae, the second largest tribe within subfamily Graphidoideae in the Graphidaceae. Adding 165 newly generated sequences from the mitochondrial small subunit rDNA (mtSSU), the nuclear large subunit rDNA (nuLSU), and the second largest subunit of the DNA-directed RNA polymerase II (RPB2), we currently distinguish 218 species among the sequenced material, including the outgroup. This corresponds to almost half the species at this point recognized within this tribe. The newly generated sequences include 23 newly described species and one newly described genus published elsewhere in this volume. For the first time, Sarcographina cyclospora Müll. Arg., in spite of its distinctly lirellate ascomata, is shown to belong in tribe Ocellularieae, as strongly supported sister to Ocellularia inturgescens (Müll. Arg.) Mangold. The following six new combinations are proposed: Melanotrema lynceodes (Nyl.) Rivas Plata, Lücking & Lumbsch, Ocellularia curranii (Vain.) Kraichak, Lücking & Lumbsch, O. khasiana (Patw. & Nagarkar) Kraichak, Lücking & Lumbsch, O. cinerea (Müll. Arg.) Kraichak, Lücking & Lumbsch, O. erodens (R. C. Harris) Kraichak, Lücking & Lumbsch, and O. laeviuscula (Nyl) Kraichak, Lücking & Lumbsch. Further, the new name Ocellularia hernandeziana Kraichak, Lücking & Lumbsch is introduced for Myriotrema ecorticatum. The nomenclatural status of the name Ocellularia microstoma is clarified.